Integrasi Mata Kuliah Bahasa Indonesia dan Teknik Penulisan Karya Ilmiah Menggunakan Model Pembelajaran Penemuan (Discovery Learning) - Ainun Syarifah; Majidatun Ahmala; Muchammad Nur Huda (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2026)
The difficulty of teaching scientific paper writing skills to students has caused researchers to try to integrate Indonesian language course with scientific paper writing techniques. The discovery learning model chosen by the researcher in implementing this integration causes the discovery model to be able to increase and maximize all capacities possessed by students to achieve goals. This study uses the action research method which is able to make researchers interpret all events in field for improvement purposes. This research was conducted at the Tarbiyah and Teacher Training Faculty of UIN Sunan Ampel Surabaya, Arabic Language Education Study Programs students totaling 71 students. The research steps used are: diagnosis, action planning, action taking, evaluation, and learning. The results showed that the use of the discovery learning model while integrating Indonesian language courses and scientific writing techniques was able to direct students to understand and practice writing scientific articles, even though students were still in semester one with very little knowledge of research methodology. Therefore, through this research, students will be able to practice scientific ethics in any writing of any scientific work. In addition, they will also get used to thinking scientifically by looking at concrete evidence first before making a decision or taking action.  Keywords: Scientific Articles; Scientific Papers; Integration of Courses